Answer:
C. x = 1/2
Explanation:
You want the solution to the equation 4x-3+5=2x+7-8x.
Solution
Subtract the entire right-side expression and simplify.
4x-3+5 -(2x+7-8x) = 0
(4 -2+8)x +(-3 +5 -7) = 0 . . . . group like terms
10x -5 = 0 . . . . . . simplify
10x = 5 . . . . . add the opposite of the constant
x = 5/10 = 1/2 . . . . . divide by the x-coefficient
The solution for x is x = 1/2.
__
Additional comment
In the end, we want the variable term(s) on one side of the equal sign, and the constant term(s) on the other side. We could take several steps to combine terms, then subtract the unwanted variable term and the unwanted constant term. It seems much easier to put them all on one side of the equal sign, where everything can be simplified at once.
The last two steps above could be reversed, giving x - 1/2 = 0, then x = 1/2.